2018
DOI: 10.1007/s11886-018-1048-x
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality as a Risk Factor in Coronary Heart Disease: a Review of Current Evidence

Abstract: Purpose of the ReviewThis review article synthesizes recent research findings on the psychological context of Type D personality and the mechanisms through which Type D affects disease progression and prognosis among patients with coronary heart disease (CHD).Recent FindingsOne in four patients with CHD has a Distressed (Type D) personality, which is characterized by two stable traits: social inhibition and negative affectivity. Type D personality predicts increased mortality and morbidity burden, and poorer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 70 publications
8
114
0
11
Order By: Relevance
“…Previous research had already established that type D patients are at higher risk of depression (Kupper & Denollet, ). The current study shows that longer pre‐hospital decision delays are one potential mechanism that increases risk of depression in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research had already established that type D patients are at higher risk of depression (Kupper & Denollet, ). The current study shows that longer pre‐hospital decision delays are one potential mechanism that increases risk of depression in this group.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the reluctance of type D patients to share feelings and worries with other people may prevent them from telling others about their symptoms and seeking medical attention. In addition, type D personality has been identified as a vulnerability factor for depression and anxiety (Kupper & Denollet, ), suggesting that patients with type D personality may be more likely to report psychological distress post‐ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety has been found to be associated with persistent chest pain, more severe cardiac symptoms, and lower rates of obstructive CAD overall among a female cohort with ischemia and a low rate of obstructive CAD [14][15][16] . In addition to anxiety, depression, anger and personality are among the most well-documented psychological risk factors associated with ischemic heart disease 12,[17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have demonstrated the role of behavioral-psychological factors on CAD [28,29], empirical studies on predictors of CAD prognosis such as MetS and its relationship with the severity of CAD are lacking, and their results are inconsistent [27,30]. Furthermore, the interconnections of different behavioral-psychological factors with different MetS components and the severity of CAD have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%